Comparison of Cognitive-Emotional Regulation, Executive Functions and Impulsivity among Students with Borderline Personality and Peers - ّBabak Keshvari; Gholamreza Sanagouye-Moharer (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Borderline personality gives rise to problems in emotion regulation, impulsivity and executive functions among students. The purpose of this study was to compare cognitive-emotional regulation, executive functions and impulsivity among students with borderline personality and their peers as control group. Materials and Methods: The present study was of post-event causal-comparative design. The statistical population consisted of students from Islamic Azad Universities in Tehran during the second half of the academic year 2016-2017, among whom 250 students were selected using convenience sampling method. Data were collected through Cognitive Ability Test, Dickman Impulsivity Test, and Borderline Personality and Emotional Regulation Questionnaire. Data were analyzed using multivariate analysis of variance by SPSS-18 software. Results: The mean (SD) age of students with borderline personality was 22.1 (4.7) and the control group 21.6 (5.1). The mean (SD) impulsivity score among students with borderline personality was 14.8 (3.1) which was higher than the control group with a mean of 10.8 (3.4) (P<0.0001). In the control group, the mean (SD) acceptance score was 16.4 (2.5), positive revaluation 15.9 (2.1), positive re-focusing 10.6 (2.3), re-focusing on planning 13.2 (2.5) and reviewing 13.1 (4.1) which were higher than the mean (SD) score of acceptance 11.6 (3.1), positive revaluation 9.6 (2.5), positive re-focusing 7.5 (2.1), the re-focus on planning is 8.6 (2.1) and the reviewing is 10.1 (4.1) of the students with borderline personality (P<0.0001). In addition, the mean (SD) score of executive functions in the control group was 13.1 (2.5) which was higher than the borderline personality group with a mean (SD) score of 8.2 (2.6) (P<0.0001). Conclusion: The study showed that the level of impulsiveness and cognitive adjustment styles of incompatible excitement was higher among students with borderline personality disorder compared to the control group. The score of executive functions and adaptive emotional adjustment styles was higher among the control group than students with borderline personality disorder. ِDOI: http://doi.org/10.22037/ch.v6i1.20747